ANALISIS MAKNA ASOSIATIF DALAM LIRIK LAGU BERSENDA GURAU KARYA RAIM LAODE : KAJIAN SEMANTIK - Aannisah Nadya Shafwah; Alda Khafifah Ritonga; Melinda Issa Bella Br. Tarigan (STKIP Subang, 2026)
This study aims to analyze the associative meanings contained in the lyrics of RaimLaode's song